2014
DOI: 10.1111/asj.12216
|View full text |Cite
|
Sign up to set email alerts
|

All‐trans retinoic acid improves goat oocyte nuclear maturation and reduces apoptotic cumulus cells during in vitro maturation

Abstract: All-trans retinoic acid (t-RA) is a natural component and representative physiologically active metabolite of vitamin A, having multiple physiologic functions. The objective of this study was to evaluate the effect of t-RA on goat oocyte maturation and cumulus cell apoptosis during in vitro maturation (IVM). Immature goat cumulus-oocyte complexes (COCs) were matured in vitro in the absence or presence of t-RA at concentrations of 10 nmol/L, 100 nmol/L and 1000 nmol/L. Oocyte maturation and embryo development w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 36 publications
1
38
0
Order By: Relevance
“…Recent in vitro studies have proposed that both all-trans and 9-cis RA can act on granulosa cells to improve oocyte maturation in several mammals, including cows [89][90][91][92][93], goats [94], pigs [95], rats [96], and mice [97,98] (reviewed in [99,100]). RARs and RXRs are expressed in granulosa cells surrounding full-grown oocytes [96,101,102].…”
Section: A Role For Ra In the Ovary After Birthmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent in vitro studies have proposed that both all-trans and 9-cis RA can act on granulosa cells to improve oocyte maturation in several mammals, including cows [89][90][91][92][93], goats [94], pigs [95], rats [96], and mice [97,98] (reviewed in [99,100]). RARs and RXRs are expressed in granulosa cells surrounding full-grown oocytes [96,101,102].…”
Section: A Role For Ra In the Ovary After Birthmentioning
confidence: 99%
“…RARs and RXRs are expressed in granulosa cells surrounding full-grown oocytes [96,101,102]. Supplementation of culture medium with all-trans or 9-cis RA induces granulosa cells to express genes that regulate differentiation and prevent apoptosis [90,[92][93][94]103,104] (reviewed in [99]), suggesting that RA acts on granulosa cells to prevent their aberrant differentiation state and apoptosis. In vivo, RARE-lacZ signal is detected in granulosa cells of mouse ovarian follicles at 3 weeks of age, and increased after injection of a gonadotropic hormone [102], supporting a role for RA on these cells.…”
Section: A Role For Ra In the Ovary After Birthmentioning
confidence: 99%
“…Retinoic acid (RA) is a metabolite of vitamin A (retinol) that mediates the functions of vitamin A, such as cell growth, development, and differentiation, and has been implicated in reproductive processes including folliculogenesis and embryonic survival [8]. In the last two decades, several reports have revealed the crucial role of the two major retinol metabolites, all- trans and 9- cis retinoic acid, on oocyte maturation and its developmental competence in different mammalian species, both in vivo and in vitro [9,10,11,12,13,14,15,16,17,18,19,20,21]. However, to the best of our knowledge, there are no reports regarding the effects of RA on camel oocytes.…”
mentioning
confidence: 99%
“…Another study, by Pauli et al () showed that oocytes obtained from follicles with higher ATRA concentrations yielded a higher percentage of embryos with higher quality grades. Further, goat oocytes treated with ATRA had increased nuclear maturation compared to control oocytes (Pu et al, ). While it has been shown that retinol treatment in vivo improves the blastocyst rate of recovered bovine COCs (Shaw et al, ), currently we are not aware of any studies investigating ATRA's effects on development.…”
Section: Discussionmentioning
confidence: 99%